Pelaksanaan Pengawasan Makanan yang Beredar pada Konsumen oleh BBPOM di Makassar (Studi Pelaksanaan UU No. 8 Tahun 1999 tentang Perlindungan Konsumen) - Amrizal; Istiqamah (Alauddin Law Development Journal (ALDEV), 2023)
This research discusses the "Implementation of Food Supervision on Consumer by BBPOM in Makassar". The purpose of this study is to understand the implementation of BBPOM supervision in Makassar regarding the circulation of expired food and the factors that hinder BBPOM in conducting supervision. This research uses a qualitative approach with field research methods and data collection through interviews. The results show that the supervision carried out by BBPOM in Makassar on food that does not meet quality standards, especially expired food, has been performed well, as evidenced by the cases discovered by BBPOM. The factors influencing BBPOM's performance in supervision are not yet optimal due to internal and external factors. The implication of this research is that the government should consider increasing the number of staff at the POM Office, with a proposal from BPOM to the government. Increasing staff numbers will have a positive impact on enhancing BPOM's performance in supervision, especially in a large working area.